The impact of personalized advertising on instagram toward brand loyalty: A study of gen z consumers - Elrizal, Mohammad Ariffa; Astuti, Rifelly Dewi (Islamic perspective on Communication and Psychology, 2024)
Background: In the digital era, social media has become an essential tool for companies to promote their brands. Social media platforms, such as Instagram, offer advertisers the ability to personalize advertisements to align more closely with target audience preferences. This research examines whether personalized advertising can enhance perceived quality and brand loyalty among Generation Z consumers exposed to brand advertisements on Instagram. Methods: Data were collected from 310 Instagram users aged 16–25 who had encountered a personalized advertisement on Instagram. Structural equation modeling (SEM) analysis was conducted using AMOS 22 software to evaluate the relationships between perceived personalization, consumer brand engagement, brand attachment, perceived quality, and brand loyalty. Findings: The results indicate that perceived personalization positively influences consumer brand engagement and brand attachment. Both consumer brand engagement and brand attachment subsequently have a positive impact on perceived quality and brand loyalty. This confirms the role of personalized advertising in building stronger consumer connections with brands on social media. Conclusion: The findings highlight the importance of personalization in social media advertising as a strategy to increase consumer engagement, attachment, and ultimately loyalty and perceived quality toward brands. Companies aiming to appeal to Generation Z can leverage personalized advertisements on Instagram to foster stronger brand relationships and consumer loyalty. Novelty/Originality of this article: This study adds to the existing literature by focusing specifically on Generation Z’s responses to personalized advertising on Instagram, exploring how perceived personalization affects engagement, attachment, quality perception, and brand loyalty in this demographic. This provides valuable insights for marketers seeking to tailor their strategies to better connect with Generation Z consumers in digital environments.